Evaluation of T and B memory cell responses elicited by the pandemic H1N1 vaccine in HIV-infected and HIV-uninfected individuals. Issue 45 (27th October 2017) - Sun, Peifang; Crum-Cianflone, Nancy F.; Defang, Gabriel; Williams, Maya; Ganesan, Anuradha; Agan, Brian K.; Lalani, Tahaniyat; Whitman, Timothy; Brandt, Carolyn; Burgess, Timothy H.
Abstract: Background: This study was to compare B and T memory cells elicited by a single dose monovalent 2009 influenza A (H1N1) vaccine (strain A/California/7/2009 H1N1) in HIV + and HIV − groups, and to analyze the impact of the prior seasonal vaccines to the immunogenicity of this vaccine. Methods: Blood samples were collected before vaccination (day 0) and at days 28 and 180. Participants were categorized into HIV − /LAIV, HIV − /TIV and HIV + /TIV subgroups according to the trivalent live-attenuated or inactivated (LAIV or TIV) seasonal influenza vaccines they received previously. The IgG + memory B cells (BMem ) and IFNγ + T cells were measured against antigens including the H1N1 vaccine, the hemagglutinin (HA) and neuraminidase (NA) proteins or peptide pools of the pandemic and the seasonal H1N1 strains, respectively. Results: Overall BMem responses increased significantly at day 28 but returned to baseline by day 180 in all three subgroups. The average frequency of the H1N1-specific BMem at day 28 for the HIV − /LAIV, HIV − /TIV and HIV + /TIV groups was 2.14%, 1.26% and 1.67%, respectively, and the average fold change was 14.39, 3.81 and 3.93, respectively. The differences of BMem between HIV − /LAIV and the two TIV subgroups were significant. For the IFNγ response, the overall spot counts ranged widely between 0 and 958/10 6 PBMCs. The group average spot counts to H1N1 vaccine was 89, 102, and 30 at day 28 for HIV − /LAIV, HIV − /TIV and HIV + /TIV subgroups, respectively. The average increase of IFNγ response at day 28 vs day 0 in all three subgroups did not reach 2-fold. Conclusion: Participants with a prior LAIV seasonal vaccine, as compared to a TIV seasonal vaccine, responded significantly better to the monovalent H1N1 vaccine. Excluding LAIV participants, no difference was seen between the HIV + and HIV − subject groups in terms of BMem . The BMem response declined at 6 months.